Early life maternal separation induces sex-specific antidepressant-like responses but has minimal effects on adult stress susceptibility in mice - Baugher, Brittany J.; Sachs, Benjamin D. (Frontiers in Behavioral Neuroscience, 2022)
Early life stress is known to increase the risk of depression and anxiety disorders, which are highly prevalent conditions that disproportionately affect women. However, the results of preclinical studies have been mixed, with some work suggesting that early life stress promotes anxiety-like behavior and/or increases susceptibility to subsequent stressors, and other research suggesting that early life stress reduces anxiety-like behavior and/or confers resilience to subsequent stress exposure. It is likely that factors such as sex and the timing and severity of early life and adult stress exposure dictate whether a particular early life experience promotes adaptive vs. maladaptive behavior later in life. Most work in this area has focused exclusively on males, but several sex differences in the effects of early life stress on subsequent stress susceptibility have been reported. The current study examined the impact of early life maternal separation on susceptibility to behavioral alterations induced by three days of variable stress in adulthood in male and female c57BL6/J mice. Our results indicate that three days of stress is sufficient to increase anxiety-like behavior in several paradigms and to increase immobility in the forced swim test. In contrast, a history of maternal separation reduces anxiety-like behavior in several tests, particularly in males. These findings could contribute to our understanding of sex differences in mental illness by demonstrating that males are more likely than females to display adaptive responses to mild early life stressors.